Balance and Adjustment between Self Efficacy, Organizational Culture, Job Design, and Work Engagement with Community Performance in Indonesia - Santi Suciningtyas; Lilik Kustiani; Fajar Supanto (International Journal Business, Management and Innovation Review, 2024)
This research aims to analyze the influence of self-efficacy, organizational culture, job design, and work engagement on people's performance in Indonesia. This research uses secondary data from the World Bank and Transparency International from 1995 to 2022. This research uses the Autoregressive Distributed Lag analysis method with a bounds testing approach. The results of this research show that self-efficacy, organizational culture, job design, and work engagement have a significant influence on the performance of society in Indonesia, both in the short and long term. Self-efficacy has a negative influence, while organizational culture, job design, and work engagement have a positive influence. The results of this study also show that there is an adjustment back to the long-term relationship between these variables after deviations occur, with an adjustment speed of 3% per period. The results of this research also show that the model used meets the classic assumptions of the Ordinary Least Square method, namely there is no autocorrelation, heteroscedasticity, multicollinearity, or model misspecification. From the results of this research, researchers recommend that the Indonesian government and society improve the quality of education and health, encourage the eradication of corruption, create attractive and useful employment opportunities, and reduce unemployment to improve the performance of society in Indonesia